Structurally modified coal char as a fuel for solid oxide-based carbon fuel cells with improved performance - Jiao, Y.; Zhao, J.; An, W.; Zhang, L.; Sha, Y.; Yang, G.; Shao, Zongping; Zhu, Z.; Li, S. (Elsevier, 2015)
Solid oxide-based carbon fuel cells (SO-CFCs) are promising devices for power generation from solid carbon with high efficiency and low emissions. Coal char is one of the most important carbon-based fuels with high abundance. In this study, to gain a better understanding of the correlation between the structure and electrochemical performance of coal char as a fuel for SO-CFCs, an industrial coal char is subjected to alkali treatment for structural modification before applying it as the fuel. It is found that after the modification, the size of carbon microcrystals is reduced, the surface area from micropores is increased, and oxygen-containing functional groups are created. All of these improvements contribute to enhanced Boudouard reactivity of the modified char and consequently improved power outputs of related cells. For example, the peak power density of a cell fueled with the modified char reaches 220 mW cm−2 at 850 °C, whereas that of a conventional coal char-fueled cell is 62 mW cm−2. The results indicate that char structure plays an important role in the performance of char-fueled SO-CFCs and that the structural modification of char through alkali treatment might be a feasible strategy to improve the applicability of coal char as a fuel for SO-CFCs.